Upper lip tie: A novel classification scale with improved inter‐rater reliability. Issue 5 (19th August 2022) - So, Raymond J.; Jenks, Carolyn; Ryan, Marisa A.; Tunkel, David E.; McKenna Benoit, Margo K.; Walsh, Jonathan M.
Abstract: Objectives: Upper lip tie (ULT) is a clinical condition with restrictive attachment of the superior labial frenulum (SLF), which may inhibit flanging of the lips. Objective outcome studies are lacking in part due to unreliable classification systems that rely solely upon a single attachment parameter of the SLF. This study's objectives are to describe a novel 3‐point classification system for ULT and compare its inter‐rater reliability to the Kotlow and Stanford systems. Methods: Five raters used the Kotlow and Stanford systems, as well as our novel 3‐point scale to score images of the SLF from 20 newborns seen at our institution between September 1, 2017 and April 1, 2018. Newborn birth weight, gestational age, and demographic data were collected from the infant's medical record. Fleiss's kappa was used to calculate inter‐rater reliability for all classification systems. Results: The parameters for our novel 3‐point classification system for ULT were as follows: length from alveolar edge to frenulum gingival attachment, length of frenulum on stretch, and free‐lip to total‐lip length ratio. Our novel scale yielded the highest inter‐rater reliability of 0.41, compared to 0.24 and 0.25 under the Kotlow and Stanford systems. Conclusion: While the Kotlow and Stanford systems are based upon a single anatomical parameter, our novel 3‐point classification scale uses three oral parameters that encompass anatomical points of attachment as well as the maximal length of the ULT on stretch. Our classification scheme is the first to incorporate a functional parameter of the SLF, and thereby more fully characterizes ULT. Level of Evidence: Level 4. Abstract : There presently lacks a reliable, comprehensive classification system for upper lip tie (ULT). Here, we present a novel 3‐point scale for ULT that incorporates both anatomical and functional parameters.